It's a Trap: Thiol‐Michael Chemistry on a DASA Photoswitch. Issue 4 (14th January 2020) - Alves, Jessica; Wiedbrauk, Sandra; Gräfe, David; Walden, Sarah L.; Blinco, James P.; Barner‐Kowollik, Christopher
Abstract: Donor–acceptor Stenhouse adducts (DASA) are popular photoswitches capable of toggling between two isomers depending on the light and temperature of the system. The cyclized polar form is accessed by visible‐light irradiation, whereas the linear nonpolar form is recovered in the dark. Upon the formation of the cyclized form, the DASA contains a double bond featuring a β‐carbon prone to nucleophilic attack. Here, an isomer selective thiol‐Michael reaction between the cyclized DASA and a base‐activated thiol is introduced. The thiol‐Michael addition was carried out with an alkyl (1‐butanethiol) and an aromatic thiol ( p ‐bromothiophenol) as reaction partners, both in the presence of a base. Under optimized conditions, the reaction proceeds preferentially in the presence of light and base. The current study demonstrates that DASAs can be selectively trapped in their cyclized state. Abstract : It's a trap : DASAs are well‐known photoswitches, which reversibly isomerize from a strongly colored linear to a colorless cyclized form upon visible‐light irradiation. The cyclized form can be readily trapped through a base‐mediated thiol‐Michael addition. The reactivity of the closed DASA towards thiol addition was found to be strongly dependent on the reaction conditions. Tuning the conditions allows the ability to selectively control the DASA reactivity in its cyclized form.